Is nalidixic acid screening still valid for the detection of reduced susceptibility of fluoroquinolone with SalmonellaTyphi? - Seema Irfan; Kausar Jabeen; Umair Anwar Jilani; Bushra Ahmed; Jaishri Mehraj; Tanwir Ahsan; Afia Zafar (Journal of Infection in Developing Countries)
Introduction: Considering the limitations of screening with nalidixic acid to detect reduced susceptibility to fluoroquinolones of Salmonella enterica serovar Typhi (S.Typhi) strains, we evaluated the use of a 30 µg nalidixic acid disc screening method in Pakistan. Methodology: Non duplicate nalidixic acid susceptible S. Typhi isolates (246) from 2003-2008 were retrieved from the Salmonella strain bank. Minimum inhibitory concentrations of ciprofloxacin for all strains were determined by agar dilution and further rechecked by ciprofloxacin E-tests.E. coli ATCC 25922 was used as the control strain. The MIC data for ciprofloxacin were compared with nalidixic acid disk (30µg) zone diameters. Results: Repeat testing of all S. Typhi isolates with a nalidixic acid (30µg) disk showed 100% susceptibility with an average zone diameter of 26 mm. Agar dilution testing revealed reduced susceptibility to ciprofloxacin, with MICs of 0.125 µg /ml for three (1.2%) isolates only. Zone sizes of strains with higher MICs were significantly lower than the strains with lower MICs (20 versus 26 mm) (p value < 0.001). Conclusion: Estimation of fluoroquinolone MICs on every nalidixic acid susceptible S. Typhi strain is not cost effective in our setting; the proportion of strains with high fluoroquinolone MICs was found to be very low. We recommend periodic fluoroquinolone MIC determination to include all isolates with a nalidixic acid borderline zone (size 20-22 mm).